2022
DOI: 10.1021/acscatal.2c02332
|View full text |Cite
|
Sign up to set email alerts
|

Tricomponent Decarboxysulfonylative Cross-coupling Facilitates Direct Construction of Aryl Sulfones and Reveals a Mechanistic Dualism in the Acridine/Copper Photocatalytic System

Abstract: Dual catalytic systems involving photocatalytic activation and transition metal-catalyzed steps have enabled innovative approaches to the construction of carbon–carbon and carbon–heteroatom bonds. However, the mechanistic complexity of the dual catalytic processes presents multiple challenges for understanding of the roles of divergent catalytic species that can impede the development of future synthetic methods. Here, we report a dual catalytic process that enables the previously inaccessible, broad-scope, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Larionov et al 54 reported a visible light-induced, dual catalytic, direct decarboxysulfonylative cross-coupling of carboxylic acids with aryl halides. This reaction includes tricomponent decarboxysulfonylative cross-coupling of carboxylic acid 31 with aryl iodide 33 occurs readily in the dual catalytic system of acridine photocatalyst and diamine ligated copper( i ) triflate, with DABCO or potassium metabisulfite 32 that results sulfone 34 with 91% yield ( Scheme 20 ).…”
Section: Synthetic Applications Of Acridinium-based Photocatalystsmentioning
confidence: 99%
“…Larionov et al 54 reported a visible light-induced, dual catalytic, direct decarboxysulfonylative cross-coupling of carboxylic acids with aryl halides. This reaction includes tricomponent decarboxysulfonylative cross-coupling of carboxylic acid 31 with aryl iodide 33 occurs readily in the dual catalytic system of acridine photocatalyst and diamine ligated copper( i ) triflate, with DABCO or potassium metabisulfite 32 that results sulfone 34 with 91% yield ( Scheme 20 ).…”
Section: Synthetic Applications Of Acridinium-based Photocatalystsmentioning
confidence: 99%
“…During the past few years, the group of Larionov led the revival of acridine photocatalysts, an old but underexploited type of catalyst, [45] for decarboxylation through proton‐coupled electron transfer (PCET) [46] . Combined with copper catalysis, they were able to achieve decarboxylative conjugate addition to Michael acceptors, [47] amination with free aryl amines (Chan–Lam type reaction), [48] amidosulfonation with O ‐benzoylhydroxylamines in the presence of immobilized SO 2 , [49] and sulfonylative coupling with aryl halides [50] . Metal‐free decarboxylative sulfinylation was also made possible with in situ generated sulfinyl sulfones (Scheme 17).…”
Section: Photoredox‐catalyzed Decarboxylationmentioning
confidence: 99%
“…We hypothesized that such a tricomponent direct decarboxylative triazolation could be accomplished by a triple catalytic process that entails direct decarboxylative azidation and subsequent cycloaddition with alkynes. However, the combination of the two processes into one multicatalytic process is challenging because of the mismatch between the oxidatively mediated azidation and the oxidant-intolerant Cu I -catalyzed cycloaddition that is instead diverted to a Glaser-type alkyne dimerization. Additionally, an efficient photocatalytic system would be needed that can both facilitate direct decarboxylation of difficult-to-oxidize carboxylic acids to bypass the typically required preactivation to more reactive carboxylic acid derivatives and also be compatible with the organoazide- and triazole-forming catalytic cycles. Importantly, the successful development of direct, tricomponent conversion of carboxylic acids to triazoles necessitates a broad-scope, direct decarboxylative azidation of carboxylic acids that is tolerant to oxidation-sensitive processes and is mediated by a simple inorganic azide source.…”
mentioning
confidence: 99%